Peningkatan Pengetahuan Gizi Pencegahan Stunting pada Ibu Hamil di Desa Serut, Kecamatan Boyolangu, Kabupaten Tulungagung - Rachma, Natasya Nishfiana; Kamila, Alfi Najah; Djunawan, Achmad; Rizki, Muhammad Risya; Indahyati, Emilia (STIKES Yayasan RS.Dr.Soetomo, 2025)
Stunting is one of the health problems that still poses a challenge in Indonesia, especially in rural areas. In Tulungagung Regency, the prevalence of stunting reached around 5.17% in 2025. Although the general stunting rate in Tulungagung has sharply decreased, there are still several villages in this area that report a relatively high stunting prevalence, reaching around 5% in Serut village. This achievement places Tulungagung as one of the regencies with a relatively high stunting rate in East Java. Dissemination to improve nutritional knowledge among pregnant mothers is an important step in preventing stunting. This study aims to prove that the dissemination of nutritional knowledge enhances nutritional knowledge for pregnant mothers in Serut Village, Boyolangu District, Tulungagung Regency. The activities used are the pre-post method using the Wilcoxon Signed Rank Test to determine the significance of the increase in understanding among pregnant mothers. Data collection in this activity uses interviews, observations, and documentation. The results show that dissemination improves nutritional knowledge for pregnant women, covering nutrition education, food assistance utilization programs, and the active role of health workers, proving that education plays an important role in increasing pregnant women's awareness of adequate nutrition fulfillment. Stakeholders need to pay attention to improving pregnant women's knowledge and access to nutritious food. It is hoped that increased nutritional knowledge can reduce the risk of stunting in children.